Usefulness of preoperative three-dimensional volumetric analysis of carotid body tumors. - Lozano-Corona, Rodrigo; Anaya-Ayala, Javier E.; Martínez-Martínez, Ricardo; López-Rocha, Sabsil; Rivas-Rojas, Melisa A.; Torres-Machorro, Adriana; Laparra-Escareno, Hugo; Hinojosa, Carlos A. (Neuroradiology, 2018)
Purpose: The Shamblin classification is the commonest method to predict complications and outcomes during carotid body tumor (CBT) resection. The aim of this study is to describe the utility of the three-dimensional volumetric reconstruction (3DVR) analysis of the CBT and its relationship with postoperative outcomes.Methods: Preoperative computed tomography angiography (CTA) was obtained to perform 3DVR of the CBT. Imaging data were analyzed and correlated with surgical outcomes: estimated blood loss (EBL), surgical time (ST), and hospital length of stay (HLOS). The Pearson test was used to determine the correlation between volume and postoperative outcomes.Results: Fifty-seven patients were studied, 13 had Shamblin type I tumors with a mean 3DVR of 7.69 cm3 (standard deviation [SD 8.27]), 21 were type II with a mean 3DVR of 15.57 cm3 (SD 8.40), and 23 were type III with a mean 3DVR of 30.58 cm3 (SD 20.16). EBL mean was 559 milliliters (mL) (standard error [SE] 80.44), the mean ST of resection was 202 min (SD 67), and the mean HLOS was 5.8 days (SD 3.23). The Pearson test showed a correlation of r = 0.69 (p < 0.0001) between 3DVR and EBL, a r = 0.4 (p = 0.05) was obtained between 3DVR and ST, and finally, a r = 0.3 (p = 0.05) between 3DVR and HLOS was obtained.Conclusion: The preoperative 3DVR determination of CBTs allows to analyze possible predictors of surgical outcomes. We found a positive correlation between the 3DVR volume and EBL. Further research is necessary to validate this method in the evaluation of these rare neoplasms.